Preparation method of aluminum oxide type ceramic chopper

By using end isocyanate polysiloxane as the binder and zirconia as the reinforced phase, ball milling and high-temperature sintering are combined with alumina, the problem of poor mechanical strength and corrosion resistance of alumina ceramic materials is solved, and high-strength and acid- and alkali-resistant ceramic materials are achieved.

CN119841627AActive Publication Date: 2025-04-18苏州芯合半导体材料有限公司
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510340398.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-21
Publication Date
2025-04-18
Estimated Expiration
2045-03-21

AI Technical Summary

Technical Problem

Alumina ceramic materials show poor mechanical strength and corrosion resistance in applications such as chopping knives.

Method used

By reacting double-terminal hydroxypropyl polysiloxane with hexamethylene diisocyanate, a terminal isocyanate polysiloxane is obtained as a binder, and with zirconia as a reinforced phase, ball milling and high-temperature sintering are combined with alumina to form a tightly connected alumina and zirconia eutectic.

Benefits of technology

It significantly improves the mechanical strength, bending strength and acid-base corrosion resistance of alumina ceramics, and is suitable for high-performance applications such as chopping knives.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the technical field of aluminum oxide ceramics, and discloses a preparation method of an aluminum oxide type ceramic chopper, which comprises the following steps: adding water, 100 parts by weight of aluminum oxide, 0.8-3 parts by weight of nano zirconium oxide and 3-6 parts by weight of isocyanate-terminated polysiloxane into a planetary ball mill, carrying out ball milling, pouring the ball-milled slurry into a mold, drying, pressing into a green body, and sintering to obtain the aluminum oxide type ceramic chopper. And sintering, grinding and polishing to obtain the aluminum oxide type ceramic chopper. The isocyanate-terminated group of polysiloxane respectively reacts with hydroxyl groups on the surfaces of aluminum oxide and nano zirconium oxide, so that the bridging and bonding effects between aluminum oxide particles and zirconium oxide nano particles are realized, the compactness and relative density of the aluminum oxide ceramic are improved, and the mechanical strength is favorably improved. Meanwhile, the aluminum oxide and the zirconium oxide which are tightly connected form a stable corrosion-resistant eutectic melt, so that the acid and alkali resistance and the corrosion resistance of the aluminum oxide ceramic and the chopper product thereof are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of alumina ceramics, in particular to a method for preparing an alumina ceramic splitting knife. Background Art

[0002] Alumina ceramics have the advantages of being lightweight, high hardness, good wear resistance, and high temperature resistance, and are widely used in ceramic cutting tools, electronic packaging, machinery manufacturing, catalyst carriers, etc. In order to improve the mechanical strength, acid and alkali corrosion resistance, and other properties of alumina ceramics, it is necessary to add binders, dispersants, reinforcing agents, etc. Common binders for alumina ceramics include polyvinyl alcohol, phenolic resin, carboxymethyl cellulose, etc. Reinforcing agents include zirconium oxide, silicon carbide, boron nitride, carbon nanotubes, etc. Chinese patent CN112939582B discloses a zirconium oxide-doped alumina ceramic and a preparation method thereof. The alumina ceramics prepared using alumina, zirconium oxide, aluminum borate whiskers, polyvinyl alcohol binder, etc. as raw materials have good fracture toughness, bending strength, and hardness, but the patent does not improve the corrosion resistance of alumina ceramics, which is not conducive to the practical application of alumina ceramics in splitters, cutting tools, etc. Summary of the invention

[0003] The invention solves the problem that the mechanical strength, corrosion resistance and other properties of the alumina ceramic material used for the splitting cutter are relatively poor.

[0004] The technical solution provided by the present invention is: a method for preparing an alumina ceramic splitting knife: (1) Add solvent, double-terminated hydroxypropyl polysiloxane and hexamethylene diisocyanate to a reaction vessel, stir and react at 70-85°C for 2-3 hours in a nitrogen atmosphere, remove low-boiling substances by vacuum distillation, and dry to obtain isocyanate-terminated polysiloxane. The reaction formula is: .

[0005] (2) Add water, 100 parts by weight of alumina, 0.8-3 parts by weight of nano zirconium oxide, and 3-6 parts by weight of isocyanate-terminated polysiloxane into a planetary ball mill for ball milling. Pour the milled slurry into a mold, dry it, and press it into a green body. The pressure is controlled to be 20-30 MPa and the pressing time is 3-6 min. Then, in a sintering furnace, first, in an air atmosphere, the temperature is increased to 1000-1200°C at a heating rate of 2-3°C / min, and the temperature is kept at this temperature for 2-3 h. Then, argon is introduced, and the pressure in the sintering furnace is controlled to be 15-20 MPa, the temperature is increased to 1400-1500°C, and the temperature is kept at this temperature for 1-2 h. After cooling, the green body is polished to obtain an alumina-type ceramic splitter.

[0006] Preferably, the solvent in (1) is toluene or tetrahydrofuran.

[0007] Preferably, the mass of hexamethylene diisocyanate in (1) is 14-17% of the mass of the dual-terminal hydroxypropyl polysiloxane.

[0008] Preferably, the ball milling speed in (2) is 300-600 r / min, and the ball milling time is 4-7 h.

[0009] Preferably, the preparation method of nano zirconium oxide is: add water and zirconium oxychloride to a hydrothermal reactor, stir and then add ammonia water to adjust the pH to 8-9, then heat to 180-210°C, react for 4-7h, cool, filter, wash with water, and dry to obtain nano zirconium oxide.

[0010] The beneficial technical effect of the present invention is as follows: the present invention reacts double-terminated hydroxypropyl polysiloxane with excess hexamethylene diisocyanate to obtain terminal isocyanate polysiloxane, uses it as a binder, and uses zirconium oxide as a reinforcing phase, which is ball-milled and blended with alumina, pressed into a billet, and sintered at high temperature to obtain alumina ceramics and its splitting knife material.

[0011] During the ball milling and molding process, the terminal isocyanate groups of polysiloxane react with the hydroxyl groups on the surface of alumina and nano-zirconia, respectively, thereby achieving bridging and bonding between alumina particles and zirconia nanoparticles, improving the interfacial bonding force between zirconia and alumina, and improving the compactness and relative density of alumina ceramics, which is beneficial to improving the mechanical strength.

[0012] The isocyanate-terminated polysiloxane of the present invention is pyrolyzed and oxidized during high-temperature sintering to generate stable silicon dioxide particles and silicon carbide, which are filled in the micropores inside the ceramic, thereby improving the compactness and playing a reinforcing role, and further improving the bending strength and mechanical properties of the alumina-type ceramic. In addition, during the high-temperature sintering process, the closely connected alumina and zirconium oxide form a stable corrosion-resistant eutectic, which significantly improves the acid and alkali resistance and corrosion resistance of the alumina ceramic and its splitter products. DETAILED DESCRIPTION

[0013] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention.

[0014] The average particle size of the following aluminum oxide is 5 μm. The average molecular weight of double-terminal hydroxypropyl polysiloxane is 3000, and the structural formula is , purchased from Hubei Langbowan Biopharmaceutical Co., Ltd.

[0015] Example 1

[0016] (1) Add 240 mL of water and 40 g of zirconium oxychloride to a hydrothermal reactor, stir, add ammonia water to adjust the pH to 8, heat to 200 ° C, react for 5 h, cool, filter, wash with water, and dry to obtain nano zirconium oxide.

[0017] (2) Add 150 mL of toluene, 30 g of double-terminated hydroxypropyl polysiloxane, and 4.2 g of hexamethylene diisocyanate into a reaction container, stir and react at 75° C. in a nitrogen atmosphere for 3 h, distill under reduced pressure, and dry to obtain isocyanate-terminated polysiloxane.

[0018] (3) Add 3L of water, 1kg of alumina, 8g of nano-zirconia, and 30g of terminal isocyanate polysiloxane into a planetary ball mill and ball mill for 4h at a speed of 500r / min; pour the slurry into a mold, dry it and press it into a green body at a pressure of 20MPa for 6min; then, in a sintering furnace, first heat it to 1100℃ in an air atmosphere at a heating rate of 2℃ / , and sinter it for 3h; then, introduce argon, control the pressure in the sintering furnace to 15MPa, heat it to 1400℃, and sinter it for 2h; after cooling, grind and polish it to obtain an alumina-type ceramic splitter.

[0019] Example 2

[0020] (1) Add 240 mL of water and 40 g of zirconium oxychloride to a hydrothermal reactor, stir, then add dropwise ammonia water to adjust the pH to 9, then heat to 180°C, react for 7 h, cool, filter, wash with water, and dry to obtain nano zirconium oxide.

[0021] (2) Add 200 mL of tetrahydrofuran, 30 g of double-terminated hydroxypropyl polysiloxane, and 5.1 g of hexamethylene diisocyanate into a reaction container, stir and react at 85° C. for 2 h in a nitrogen atmosphere, distill under reduced pressure, and dry to obtain isocyanate-terminated polysiloxane.

[0022] (3) Add 3L of water, 1kg of alumina, 14g of nano-zirconia, and 38g of terminal isocyanate polysiloxane into a planetary ball mill and ball mill for 4h at a speed of 600r / min; pour the slurry into a mold, dry it and press it into a green body at a pressure of 30MPa for 3min; then, in a sintering furnace, first heat it to 1000℃ at a heating rate of 2℃ / min in an air atmosphere and sinter it for 3h; then, introduce argon and control the pressure in the sintering furnace to 20MPa, heat it to 1450℃ and sinter it for 2h; then, grind and polish it after cooling to obtain an alumina-type ceramic splitter.

[0023] Example 3

[0024] (1) Add 280 mL of water and 40 g of zirconium oxychloride to a hydrothermal reactor, stir, add ammonia water to adjust the pH to 8, heat to 210°C, react for 4 hours, cool, filter, wash with water, and dry to obtain nano zirconium oxide.

[0025] (2) Add 200 mL of toluene, 30 g of double-terminated hydroxypropyl polysiloxane, and 4.7 g of hexamethylene diisocyanate into a reaction container, stir and react at 70° C. in a nitrogen atmosphere for 3 h, distill under reduced pressure, and dry to obtain terminal isocyanate polysiloxane.

[0026] (3) Add 3.5L of water, 1kg of alumina, 20g of nano zirconium oxide, and 45g of terminal isocyanate polysiloxane into a planetary ball mill and ball mill for 7h at a speed of 300r / min; pour the slurry into a mold, dry it and press it into a green body at a pressure of 20MPa for 6min; then, in a sintering furnace, first heat it to 1200℃ at a heating rate of 3℃ / min in an air atmosphere and sinter it for 2h; then, introduce argon and control the pressure in the sintering furnace to 15MPa, heat it to 1400℃ and sinter it for 2h; after cooling, grind and polish it to obtain an alumina-type ceramic splitter.

[0027] Example 4

[0028] (1) Add 4L of water, 1kg of alumina, 25g of nano zirconium oxide (prepared in the same manner as in Example 1), and 53g of terminal isocyanate polysiloxane (prepared in the same manner as in Example 1) into a planetary ball mill, and mill for 5h at a speed of 600r / min; pour the slurry into a mold, dry it, and press it into a green body at a pressure of 20MPa for a pressing time of 5min; then, in a sintering furnace, first, heat it to 1100°C in an air atmosphere at a heating rate of 2°C / min, and sinter it at this temperature for 2h; then, introduce argon, control the pressure in the sintering furnace to 20MPa, heat it to 1500°C, and sinter it at this temperature for 1h; and after cooling, grind and polish it to obtain an alumina-type ceramic splitter.

[0029] Example 5

[0030] (1) Add 4L of water, 1kg of alumina, 30g of nano zirconium oxide (prepared in the same manner as in Example 1), and 60g of terminal isocyanate polysiloxane (prepared in the same manner as in Example 1) into a planetary ball mill, and mill for 5h at a speed of 600r / min; pour the slurry into a mold, dry it, and press it into a green body at a pressure of 25MPa for a pressing time of 5min; then, in a sintering furnace, first, heat it to 1000°C in an air atmosphere at a heating rate of 2°C / min, and sinter it at this temperature for 3h; then, introduce argon, control the pressure in the sintering furnace to 15MPa, heat it to 1500°C, and sinter it at this temperature for 1h; after cooling, grind and polish it to obtain an alumina-type ceramic splitter.

[0031] Comparative Example 1: (1) Add 3L of water, 1kg of alumina, and 30g of isocyanate-terminated polysiloxane to a planetary ball mill and mill for 4h at a speed of 500r / min; pour the slurry into a mold, dry it, and press it into a green body at a pressure of 20MPa for 6min; then, in a sintering furnace, first heat it to 1100℃ in an air atmosphere at a heating rate of 2℃ / , and sinter it for 3h; then, introduce argon, control the pressure in the sintering furnace to 15MPa, heat it to 1400℃, and sinter it for 2h; after cooling, grind and polish it to obtain an alumina-type ceramic splitter.

[0032] Comparative Example 2: (1) Add 3L of water, 1kg of alumina, and 8g of nano-zirconia into a planetary ball mill and mill for 4h at a speed of 500r / min; pour the slurry into a mold, dry it and press it into a green body at a pressure of 20MPa for 6min; then, in a sintering furnace, first heat it to 1100℃ in an air atmosphere at a heating rate of 2℃ / min and sinter it for 3h; then, introduce argon and control the pressure in the sintering furnace to 15MPa, heat it to 1400℃ and sinter it for 2h; then, grind and polish it after cooling to obtain an alumina-type ceramic splitter.

[0033] Comparative Example 3: (1) Add 3L of water, 1kg of alumina, 8g of nano zirconium oxide, and 30g of double-terminal hydroxypropyl polysiloxane to a planetary ball mill and ball mill for 4h at a controlled speed of 500r / min; pour the slurry into a mold, dry it and press it into a green body at a controlled pressure of 20MPa for 6min; then, in a sintering furnace, first heat it to 1100℃ in an air atmosphere at a heating rate of 2℃ / , and sinter it for 3h; then, introduce argon, control the pressure in the sintering furnace to 15MPa, heat it to 1400℃, and sinter it for 2h; after cooling, grind and polish it to obtain an alumina-type ceramic splitter.

[0034] Performance Test: Alumina ceramic samples were prepared according to the raw materials and processes of the embodiments and comparative examples. Specifically, the "grinding and polishing after cooling" in the embodiments and comparative examples was adjusted to "cooling", and the other steps remained unchanged.

[0035] Specifically: Taking Example 1 as an example: add 3L of water, 1kg of alumina, 8g of nano zirconium oxide, and 30g of terminal isocyanate polysiloxane into a planetary ball mill, and ball mill for 4 hours, controlling the rotation speed to 500r / min; pour the slurry into a mold, and press it into a green body after drying, controlling the pressure to 20MPa, and the pressing time to 6min; then in a sintering furnace, first in an air atmosphere, at a heating rate of 2℃ / , the temperature is increased to 1100℃, and the temperature is kept sintered for 3h; then argon is introduced, and the pressure in the sintering furnace is controlled to 15MPa, the temperature is increased to 1400℃, and the temperature is kept sintered for 2h; cool to obtain an alumina type ceramic sample.

[0036] The relative density of alumina ceramic samples was tested according to the Archimedes method. Each sample was tested 5 times and the average value was taken.

[0037] The three-point bending method was used to test the flexural strength of alumina ceramic samples. The sample size was 35 mm × 4 mm × 3 mm, and the loading rate was 0.5 mm / min.

[0038] The acid and alkali corrosion resistance of alumina ceramics was tested according to the method of GB / T 1970-1996. The medium for the acid corrosion test was a 20% mass fraction sulfuric acid solution. The medium for the alkali corrosion test was a 1% mass fraction sodium hydroxide solution. The boiling time was 1h. The mass loss method was used to calculate the percentage of mass reduction compared to the mass before corrosion, i.e., the corrosion mass loss rate. The smaller the corrosion mass loss rate, the better the acid and alkali resistance and corrosion resistance.

[0039] Table 1 Alumina ceramic performance test

[0040] After testing, in Examples 1-5, the isocyanate-terminated polysiloxane is used as a binder and zirconium oxide is used as a reinforcing phase. During the ball milling and blank making process, the isocyanate-terminated polysiloxane reacts with the hydroxyl groups on the surface of alumina and nano-zirconia, respectively, thereby achieving a bridging and bonding effect between alumina particles and zirconium oxide nanoparticles, improving the interfacial bonding force between zirconium oxide and alumina, improving the compactness and relative density of alumina ceramics, and being beneficial to improving mechanical strength. At the same time, during the high-temperature sintering process, the polysiloxane is pyrolyzed and oxidized at high temperature to generate stable silicon dioxide particles and silicon carbide, which are filled in the micropores inside the ceramic, can improve compactness, play a reinforcing role, and further improve the bending strength and mechanical properties of alumina-type ceramics. In addition, during the high-temperature sintering process, the tightly connected alumina and zirconium oxide form a stable corrosion-resistant eutectic, which significantly improves the acid and alkali resistance and corrosion resistance of alumina.

[0041] Compared with Example 1, Comparative Example 1 did not add nano zirconium oxide, and the acid resistance and corrosion resistance of the alumina ceramic were poor. Comparative Example 2 did not add the end isocyanate polysiloxane binder, the interface bonding force between zirconium oxide and alumina was weak, the compactness and relative density of the alumina ceramic were low, and the flexural strength was poor. The double-terminated hydroxypropyl polysiloxane of Comparative Example 3 does not contain an isocyanate group, and cannot react with alumina and the hydroxyl groups on the surface of nano zirconium oxide, and cannot achieve the bridging and bonding effect between alumina particles and zirconium oxide nanoparticles, and does not improve the interface bonding force between zirconium oxide and alumina, resulting in low compactness and relative density of the alumina ceramic, and poor flexural strength.

[0042] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, a person skilled in the art may make non-creative modifications to the present embodiment as needed, and such modifications shall be protected by the patent law as long as they are within the scope of protection claimed in the present application.

Claims

1. A method for preparing an alumina ceramic splitter, characterized in that: The preparation method is: (1) adding a solvent, a double-terminated hydroxypropyl polysiloxane and hexamethylene diisocyanate into a reaction container, reacting in a nitrogen atmosphere, performing reduced pressure distillation, and drying to obtain an isocyanate-terminated polysiloxane; (2) Add water, 100 parts by weight of alumina, 0.8-3 parts by weight of nano zirconium oxide, and 3-6 parts by weight of isocyanate-terminated polysiloxane into a planetary ball mill for ball milling. Pour the milled slurry into a mold, press it into a green body after drying, and then sinter it in a sintering furnace. After cooling, grind and polish it to obtain an alumina-type ceramic splitter.

2. The method for preparing an alumina ceramic splitting knife according to claim 1, characterized in that: The solvent in (1) is toluene or tetrahydrofuran.

3. The method for preparing an alumina ceramic splitting knife according to claim 1, characterized in that: The mass of the hexamethylene diisocyanate in (1) is 14-17% of the mass of the double-terminal hydroxypropyl polysiloxane.

4. The method for preparing an alumina ceramic splitting knife according to claim 1, characterized in that: The reaction temperature in (1) is 70-85°C and the reaction time is 2-3h.

5. The method for preparing an alumina ceramic splitting knife according to claim 1, characterized in that: The rotation speed of the ball mill in (2) is 300-600 r / min, and the ball milling time is 4-7 h.

6. The method for preparing an alumina ceramic splitting knife according to claim 1, characterized in that: The pressure during pressing of the green body in (2) is 20-30 MPa and the time is 3-6 min.

7. The method for preparing an alumina ceramic splitting knife according to claim 1, characterized in that: The sintering in (2) is first carried out in an air atmosphere at a heating rate of 2-3°C / min to a temperature of 1000-1200°C and kept at that temperature for 2-3 hours; then argon is introduced and the pressure in the sintering furnace is controlled at 15-20MPa, and the temperature is raised to 1400-1500°C and kept at that temperature for 1-2 hours.

8. The method for preparing an alumina ceramic splitting knife according to claim 1, characterized in that: The preparation method of the nano zirconium oxide is as follows: adding water and zirconium oxychloride into a hydrothermal reaction kettle, stirring and then dropping ammonia water to adjust the pH to 8-9, then heating to 180-210° C., reacting for 4-7 hours, cooling, filtering, washing with water, and drying to obtain the nano zirconium oxide.

Citation Information

Patent Citations

  • A zirconium-doped alumina ceramic and its preparation method

    CN112939582B

  • Thermal conduction film binder used for heat repairing

    CN103740312A

  • 3D printing method of high-strength ceramic body

    CN109485395A

  • High-performance aluminum oxide ceramic chopper and preparation method thereof

    CN116003109A

  • Modified epoxy resin adhesive and its preparation process

    CN1670109A